(untitled) (Research, Society and Development, 2021)
Mimosa caesalpiniifolia Benth. (Fabaceae) is a tree native to the semiarid region of Northeast Brazil, which presents growing economic potential for the exploitation of timber and non-timber forest products. The presence of aggressive prickles in most plants of this species makes it difficult to manage the stands, but there are specimens without prickles that can be used to get around this inconvenience. Our objective was to determine the phenotypic frequency of the character absence/presence of prickles in progenies of free pollination of a cultivated population of M. caesalpiniifolia, and to access the genetic diversity of individuals of the phenotype without prickles of this population. Genetic diversity was accessed using molecular markers Inter Simple Sequence Repeat (ISSR) and phenotyping for the presence/absence of prickles was determined in young individuals from nine free-pollination progenies from three phenotype trees with prickles and six phenotype trees without prickles. The Shannon index (I), Nei genetic diversity (He), percentage of polymorphic bands (P) and Nei genetic identity were calculated. The absence of prickles (77%) was higher that presence prickles (23%). The predominance of the absence of prickles phenotype and the moderate levels of genetic diversity (P = 64%; He = 0.208 and I = 0.315) among individuals with this phenotype may be because of artificial selection for the absence of prickles phenotype in the source population.